2023
DOI: 10.1097/ms9.0000000000001088
|View full text |Cite
|
Sign up to set email alerts
|

Non-adherence to anti-hypertensive medications in a low-resource country Nepal: a systematic review and meta-analysis

Pashupati Pokharel,
Saroj Kumar Jha,
Alisha Adhikari
et al.

Abstract: Background: Nepal is a low resource country with cardiovascular diseases being the number one cause of mortality. Despite hypertension being the single most important risk factor for cardiovascular diseases, non-adherence to anti-hypertensive medications has not been assessed systematically. So, this systematic review and meta-analysis aims to analyze the prevalence of non-adherence to anti-hypertensive medications in Nepal. Methodology: This systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The study done in the community setting of Nepal reported that 37.5% [ 12 ] of hypertensive patients had a high level of adherence whereas in a hospital setting, only 23.9% [ 13 ] of hypertensive patients had a high level of adherence. The recent meta-analysis of Nepal reported that half of the hypertensive population of Nepal is non-adherent to their anti-hypertensive medications, posing a higher risk of cardiovascular events [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study done in the community setting of Nepal reported that 37.5% [ 12 ] of hypertensive patients had a high level of adherence whereas in a hospital setting, only 23.9% [ 13 ] of hypertensive patients had a high level of adherence. The recent meta-analysis of Nepal reported that half of the hypertensive population of Nepal is non-adherent to their anti-hypertensive medications, posing a higher risk of cardiovascular events [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is crucial to identify the factors associated with adherence to antihypertensive medication to improve the control of blood pressure among patients with hypertension in Nepal [ 14 ]. Several studies have reported the presence of co-morbidity, alcohol consumption, self-purchasing of medications [ 7 , 14 ], forgetfulness [ 13 , 14 ], unavailability of hypertensive medicines at the nearest health facilities [ 15 ], large number of medications prescribed, irregular follow-up [ 16 , 17 ], etc., were all linked to non-adherence to antihypertensive medication and all identified factors were modifiable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation